2016
DOI: 10.1021/acs.jmedchem.5b01629
|View full text |Cite
|
Sign up to set email alerts
|

Designed Glycopeptidomimetics Disrupt Protein–Protein Interactions Mediating Amyloid β-Peptide Aggregation and Restore Neuroblastoma Cell Viability

Abstract: How anti-Alzheimer's drug candidates that reduce amyloid 1-42 peptide fibrillization interact with the most neurotoxic species is far from being understood. We report herein the capacity of sugar-based peptidomimetics to inhibit both Aβ1-42 early oligomerization and fibrillization. A wide range of bio- and physicochemical techniques, such as a new capillary electrophoresis method, nuclear magnetic resonance, and surface plasmon resonance, were used to identify how these new molecules can delay the aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 59 publications
6
58
0
Order By: Relevance
“…31 We focused our attention on three kinds of species: (1) the monomer (peak ES), (2) different small metastable oligomers grouped under peak ES′ and (3) transient species formed later and which correspond to species larger than dodecamers but still soluble (peak LS). Aggregation kinetics of Aβ 1–42 peptide alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31 We focused our attention on three kinds of species: (1) the monomer (peak ES), (2) different small metastable oligomers grouped under peak ES′ and (3) transient species formed later and which correspond to species larger than dodecamers but still soluble (peak LS). Aggregation kinetics of Aβ 1–42 peptide alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, whereas TEM analyses have been used to reveal the formation and morphology of higher molecular weight and insoluble Aβ aggregates, we have recently reported a CE method to monitor the early steps of the oligomerization process over time, and, in particular, the formation of small soluble oligomers . This technique allows an evaluation of the impact of small molecules on three key species, (1) the monomer of Aβ 1–42 (peak ES), (2) different small metastable oligomers grouped under peak ES′, and (3) transient later species corresponding to oligomers larger than dodecamers (peak LS) , . Aggregation kinetics of Aβ 1–42 alone showed that, over time, the peak of monomer ES decreased in favor of the peaks of oligomers ES′ and LS, and that soluble species were no longer detected after 6 h (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of peptides that specifically target Aβ have been reported in the literature, among these, inhibitors based on the hydrophobic core sequence of Aβ have been modified using a variety of different ways including peptide chain cyclization, N‐Alkylation, introduction of non‐natural aminoacid, addition of basic or acid homopeptides at N‐or C‐termini, conjugation with a number of natural and synthetic small molecules . To our knowledge, peptide based inhibitors bearing glyosidic moieties are less represented . In our previous work, we described some chief advantages of the trehalose conjugated peptide inhibitors in terms of water solubility, selectivity toward Aβ peptides with dose response antifibrillogenic activity and enhanced resistance to proteases in biological fluids .…”
Section: Discussionmentioning
confidence: 99%